2010
DOI: 10.1128/jcm.01953-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Francisella tularensis by Whole-Cell Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry: Fast, Reliable, Robust, and Cost-Effective Differentiation on Species and Subspecies Levels

Abstract: Francisella tularensis, the causative agent of tularemia, is a potential agent of bioterrorism. The phenotypic discrimination of closely related, but differently virulent, Francisella tularensis subspecies with phenotyping methods is difficult and time-consuming, often producing ambiguous results. As a fast and simple alternative, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) was applied to 50 different strains of the genus Francisella to assess its ability to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
69
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 33 publications
(35 reference statements)
8
69
0
3
Order By: Relevance
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 83%
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 83%
“…F. tularensis cultures (100%) were differentiated at the species level in the locally generated custom database, while the proprietary Bruker Biotyper database identified only 56% of the F. tularensis cultures at the species level. This result agrees with the result of Seibold et al (16), who identified cultures of Francisella spp. to the species level with a supplemented Biotyper database.…”
supporting
confidence: 93%
“…Therefore, accurate assays for microbial identification are important to ensure proper medical intervention, either in the case of a natural outbreak or an intentional release. Such assays must be able to identify unambiguously a broad panel of potential threat microorganisms in different background matrices that may or may not be contaminated with non-HPB bacteria (11).Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is a rapid, accurate, sensitive, and cost-effective method that offers an adequate alternative to genome-based approaches and that has been widely used for identification and typing of microorganisms in a clinical routine setup (12-19), as well as for HPB (20)(21)(22)(23)(24)(25)(26)(27). This method does …”
mentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is a rapid, accurate, sensitive, and cost-effective method that offers an adequate alternative to genome-based approaches and that has been widely used for identification and typing of microorganisms in a clinical routine setup (12)(13)(14)(15)(16)(17)(18)(19), as well as for HPB (20)(21)(22)(23)(24)(25)(26)(27). This method does not depend on exclusive consumables and has revealed high levels of reproducibility in both intralaboratory and interlaboratory studies (28,29).…”
mentioning
confidence: 99%